Acoustic levitation : from physics to applications - Zang, Duyang (Singapore : Springer, 2020)
This book systematically introduces readers to the fundamental physics and a broad range of applications of acoustic levitation, one of the most promising techniques for the container-free handling of small solid particles and liquid droplets. As it does away with the need for solid walls and can easily be incorporated into analysis instruments, acoustic levitation has attracted considerable research interest in many fields, from fluid physics to material science. The book offers a comprehensive overview of acoustic levitation, including the history of acoustic radiation force; the design and development of acoustic levitators; the technology's applications, ranging from drop dynamics studies to bio/chemical analysis; and the insightful perspectives that the technique provides. It also discusses the latest advances in the field, from experiments to numerical simulations. As such, the book provides readers with a clearer understanding of acoustic levitation, while alsostimulating new research areas for scientists and engineers in physics, chemistry, biology, medicine and other related fields.
Keywords: INGENIERÍA ACÚSTICA; MECANICA DE FLUIDOS; FLUIDOS